Infective endocarditis: prevention and antibiotic prophylaxis - Swiss Medical Weekly; Sendi, Parham; Hasse, Barbara; Frank, Michelle; Flückiger, Ursula; Boggian, Katia; Guery, Benoit; Jeger, Raban; Zbinden, Stephan; Agyeman, Philipp; Knirsch, Walter; Greutmann, Matthias (Swiss medical weekly, 2021)
The Swiss societies of Infectious Diseases, Pediatric Cardiology and Cardiology and the Pediatric Infectious Disease Group of Switzerland present the current update on infective endocarditis prophylaxis in a joint initiative. The major focus of the revised recommendations is a comprehensive prevention campaign for all patients at risk for infective endocarditis. Antibiotic prophylaxis is recommended only for individuals at high risk. Within this high-risk group there is a ranking order, and the conditions are presented accordingly. Antibiotic prophylaxis is no longer recommended for patients with unrepaired ventricular septal defects and patent ductus arteriosus. Recommendations for antibiotic prophylaxis for the prevention of infective endocarditis are categorized in dental and non-dental interventions.